Interprofessional education in practice: Evaluation of a work integrated aged care program. (March 2016) - Lawlis, Tanya; Wicks, Alison; Jamieson, Maggie; Haughey, Amy; Grealish, Laurie
Abstract: Health professional clinical education is commonly conducted in single discipline modes, thus limiting student collaboration skills. Aged care residential facilities, due to the chronic and complex health care needs of residents, provide an ideal placement to provide a collaborative experience. Interprofessional education is widely acknowledged as the pedagogical framework through which to facilitate collaboration. The aim of the evaluation was to assess student attitudes towards collaboration after active involvement in an interprofessional education program. Students studying nursing, occupational therapy, and aged care were invited to complete a version of the Readiness for Interprofessional Learning Scale before and after participating in a three-week pilot interprofessional program. A positive change in student attitudes towards other health professionals and the importance of working in interprofessional teams was reported with significant differences between two statements indicated: Learning with health-care students before qualifications would improve relationships after qualifications ; and I learned a lot from the students from the other disciplines . The innovative pilot project was found to enhance student learning in interprofessional teams and the aged care environment. Further development of this and similar interprofessional programs is required to develop sustainable student projects that have health benefits for residents in aged care residential facilities.